Relationship between symptom-onset-to-balloon time and outcomes in patients with acute myocardial infarction treated with primary percutaneous coronary intervention. (25th November 2020) - Hromadka, M; Motovska, Z; Hlinomaz, O; Kala, P; Varvarovsky, I; Dusek, J; Svoboda, M; Jarkovsky, J; Tousek, F; Majtan, B; Simek, S; Branny, M; et al.
Abstract: Background: Time delay is an important prognostic factor and indicator of quality of care for patients with AMI indicated for primary percutaneous coronary intervention (PCI). Purpose: Assessment of total ischaemia time and its relationship to catheterization findings and the incidence of ischaemic events within 1 year in patients treated with primary PCI. Method: The analysis included 1230 patients with AIM and primary PCI randomized in the Prague-18 study (prasugrel vs. ticagrelor). We evaluated the total ischaemia time and two the intermediate intervals: A - from the symptom onset to the arrival to the hospital and B - from the entry the hospital to balloon time. We assessed the time delay in relation to patient characteristics, PCI results and ischaemic endpoints (death, reIM, stroke) within 30 days and 1 year. Results: Median total ischaemia time was 3.2 hours. Its prolongation resulted in more frequent incidence of TIMI flow <2 before PCI (p=0.029), TIMI flow <3 after PCI (p=0.004) and suboptimal PCI (p=0.018). The interval A was significantly prolonged in women (p=0.001) and obese patients with BMI ≥30 kg / m 2 (p=0.001). The interval B <30 min was achieved in 70% of patients, only 5.3% had interval >90 min. In 717 (61, 6%) patients with increased risk (at least 1 criterion: age >70 years, STEMI anterior wall or LBBB, Killip II-IV, history of MI and CABG, SBP <100 mmHG and HR >100 / min), the prolongation of total ischaemia time (≤2 vs. 2.1–4 vs. 4.1–6 vs. >6 hours) resulted in a more frequent incidence of combined ischaemic endpoints within 1 year (p=0.034) and left ventricular systolic dysfunction (p=0.028). Conclusion: The extension of total ischaemia time in patients treated with primary PCI resulted in a more frequent suboptimal result with TIMI flow <3. Female gender, older age and obesity in women were associated with an increase in total ischaemia time. In patients with increased risk, time delay resulted in a higher incidence of combined ischaemic endpoints within 1 year and left ventricular systolic dysfunction. Funding Acknowledgement: Type of funding source: None